2018
DOI: 10.5123/s2176-62232018000100005
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do pré-natal quanto à detecção de sífilis e HIV em gestantes atendidas em uma área rural do estado do Pará, Brasil

Abstract: OBJETIVOS: Avaliar a assistência pré-natal prestada, em relação à sífilis e à infecção pelo HIV, às gestantes atendidas em uma Estratégia Saúde da Família de Ananindeua, estado do Pará, Brasil, em 2015, verificando o perfil das mesmas e a prevalência dessas doenças. MATERIAIS E MÉTODOS: Trata-se de um estudo retrospectivo, observacional e transversal, realizado por meio de análise dos prontuários de 41 gestantes que terminaram o pré-natal no ano de 2015. RESULTADOS: As gestantes tinham, em sua maioria, entre 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
24

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 6 publications
1
8
0
24
Order By: Relevance
“…The inequity in health care utilization is more concentrated in the secondary level 13, 14,42,43 . Studies in Brazil also showed difficulties in implementing rapid tests in primary care 33,44,45 . The different results might be explained by the long waiting barrier to access secondary care in the brazilian healthcare system 13, 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The inequity in health care utilization is more concentrated in the secondary level 13, 14,42,43 . Studies in Brazil also showed difficulties in implementing rapid tests in primary care 33,44,45 . The different results might be explained by the long waiting barrier to access secondary care in the brazilian healthcare system 13, 43 .…”
Section: Discussionmentioning
confidence: 99%
“…One reiterates the importance of the active participation and the articulation between the PHC services and the specialized, in order that one can overcome the fragmentation of the actions of attention to health 32 , including reproductive and of management of infection, envisioning the woman who experiences these conditions, in search of the integrality of the care. 33 One emphasizes the services integration for attention to the people living with HIV 34 , in which in the specificity of the women population must be since the attention to the sexual and reproductive health 35 , anti-HIV testing 36,37 and continuity of attention in the puerperal period. 38 These integrated actions among the services should compose the care lines to the women.…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of prenatal care, it is recommended to request tests at an appropriate time to prevent and treat diseases in a timely manner. 15 Among the previous pathologies associated with pregnancy, five had Systemic Arterial Hypertension and two Diabetes Mellitus. Pregnancy can stimulate SAH in previously normotensive women or worsen a picture of previous chronic hypertension.…”
Section: Rio De Janeiro Rj Brasil 2014mentioning
confidence: 99%
“…Far from representing an abstraction or utopia of difficult materialization, welcoming is translated into simple gestures with a cordial form of care, in which professionals call pregnant women by name, inform about conducts and procedures to be performed through an appropriate language, they listen and value the users' narratives, guarantee their privacy, among other humanized attitudes that can be operated, if respected the ethics of otherness. 3,15,17…”
Section: Rio De Janeiro Rj Brasil 2014mentioning
confidence: 99%